DINAMIKA SOSIAL BUDAYA MASYARAKAT MELAYU PESISIR (Studi Pengelolaan Madu Sialang di Desa Rawa Mekar Jaya) - T. Romi Marnelly (Universitas Andalas, 2017)
All societies experience the change. But also with the society that is in the village of Rawa Mekar Jaya, Subdistrict of Sungai Apit, Regency of Siak. Here, there is unique tradition that is called menumbai interrelated the use of sialang’s honey bee. Together with the age development, this tradition starts to have dynamics. So that the questions come 1) What kind of aspects that experience the cultural social change in the processing activity of sialang’s honey bee in the village of Rawa Mekar Jaya Then, what kind of factors that push that change?. The research method that is used is descriptive qualitative. The location election in the village of Rawa Mekar Jaya because this location has sialang’s tree and the activity that is involved with the sialang’s honey. The research subject consists of the village chief, society figure, owner of sialang trunk and sialang’s trunk climber. The Data Collecting Technics are such as observation and deep interview. The sampling technic is namly purposive sampling. Based on the research result, it can be known that the aspects that experience the change in the processing activity of sialang’s honey is aspect of language, knowledge, tools and life equipment, economy system and religion system. Meanwhile, the factors that push the change is the contact with another culture, unsatisfication of society towards certain life sectors, future orientation and value that the human should struggle to fix the life.